Lepidic, Papillary Components and EGFR Mutations are Frequent in Patients With Lung Adenocarcinoma Who are Over 75 Years Old. Issue 9 (October 2019) - Forest, Fabien; Patoir, Arnaud; Dal-Col, Pierre; Da Cruz, Vanessa; Camy, Florian; Stachowicz, Marie-Laure; Bayle-Bleuez, Sophie; Fournel, Pierre; Karpathiou, Georgia; Péoc'h, Michel
Abstract : Treatment for lung adenocarcinoma frequently diverges from standard treatment in older patients. Clinical, pathologic, and molecular characteristics of lung cancer in patients over 75 years old have not been fully described. The aim of our work was to describe the rate of EGFR, KRAS, BRAF V600, and HER2 mutations, and ALK rearrangement and pathologic characteristics in patients with lung adenocarcinoma over 75, compared with patients below 75 years old. This is a retrospective study from 2 cohorts: a histopathologic cohort of all consecutively resected lung adenocarcinoma in our institution for patients over 75 (n=54, from 2006 to 2017) compared with patients below 75 years old (n=148, from 2014 to 2017) and a molecular cohort of all stage IIIb or IV lung adenocarcinoma from 2009 to 2017 (n=1611). Papillary and lepidic components were more frequently found in patients over 75 years old ( P =0.046 and 0.0078, respectively). The rate of current smokers was lower in older patients ( P <0.0001). EGFR mutations were more frequent in patients over 75 than in younger patients: 17% versus 8.1% ( P <0.0001). The mutually exclusive KRAS mutation was more frequent in patients below 75 years old than in older patients: 25.8% versus 12.8% ( P <0.0001). There was no difference for the proportion of the 2 most frequent EGFR mutations (exon 19 deletion and L858R mutation) ( P =0.85) or KRAS-mutated codon ( P =0.22) between tumors in younger or older patients. There was no statistically significant difference for the presence of BRAF V600, HER2 mutations, and ALK rearrangement ( P =0.44, 0.71, and 1, respectively). Our work highlights the fact that EGFR mutations are more frequent in patients over 75 years old in our population. We can hypothesize that this difference might be mainly caused by the less frequent occurrence of tobacco-smoking–related lung cancers in the elderly and the presence of a lepidic or papillary component in this age group.